Pengaruh Motivasi, Disiplin Kerja dan Beban Kerja Terhadap Kinerja Pegawai pada Fakultas Sains dan Teknologi UIN Sunan Ampel Surabaya - Edika Aferi; Sri Rahayu; Rifda Fitrianty; Fanny Dwi Puspitasari (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
The objective of this study is to determine the effect of work motivation, work discipline, and workload on employee performance at the Faculty of Science and Technology, UIN Sunan Ampel Surabaya. The subjects of the study were all employees, both civil servants and non-civil servants, within the Faculty of Science and Technology, UIN Sunan Ampel Surabaya, totaling 123 people selected using probability sampling and a saturated sampling technique. Data were collected through questionnaires and analyzed using multiple linear regression. The results showed that each variable significantly influenced employee performance at the Faculty of Science and Technology, UIN Sunan Ampel Surabaya, when examined individually. Simultaneously, the variables of motivation, discipline, and workload had a significant effect on employee performance, with discipline being the most dominant variable at 41%. The model's R-square was 0.672, meaning 67% of the variation in employee performance could be explained by changes in motivation, discipline, and workload, while the remaining 33% was influenced by other factors not included in the model.